GE_GERICHTE P/8497/2015 vom 8. Mai 2015 - GE Cour de justice (2015)
RISQUE DE COMMISSION; PROPORTIONNALITÉ; MESURE PROVISIONNELLE; DÉBAT DU TRIBUNAL; FORME ORALE | CPP.221; CPP.304; CPP.388; CPP.397; CP.30; CP.180